2015
DOI: 10.1590/1677-5449.02715
|View full text |Cite
|
Sign up to set email alerts
|

Cirurgia aberta e endovascular no tratamento de aneurisma de artéria poplítea: experiência de cinco anos do HCRP-FMRP-USP

Abstract: Background: popliteal artery aneurysms (PAAs) account for 70% of peripheral aneurysms. Surgery is indicated for aneurysms that have diameters greater than 2.0 cm or are symptomatic. Repair can be achieved by conventional surgical techniques or using endovascular methods, which are becoming increasingly popular, but for which there is not yet a consensus on indications. Objective: To describe the experience of treating PAAs at the vascular and endovascular surgery department of the Hospital das Clínicas de Ribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The six articles describing retrospective studies were published by Pulli et al, 15 Huang et al, 16 Serrano Hernando et al, 17 Ronchey et al, 18 Cervin et al, 19 and Braga et al, 13 and are summarized in Tables 1 and 2. The metanalyses used were conducted by von Stumm et al, 20 published in 2015 and combining a total of 652 cases, and by Leake et al, 21 published in 2017, covering 14 studies and 4,880 PAA treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The six articles describing retrospective studies were published by Pulli et al, 15 Huang et al, 16 Serrano Hernando et al, 17 Ronchey et al, 18 Cervin et al, 19 and Braga et al, 13 and are summarized in Tables 1 and 2. The metanalyses used were conducted by von Stumm et al, 20 published in 2015 and combining a total of 652 cases, and by Leake et al, 21 published in 2017, covering 14 studies and 4,880 PAA treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Braga et al 13 reported 5 years' experience at the Hospital das Clínicas de Ribeirão Preto. Endovascular treatment using Viabahn  covered stents (a mean of 1.6 stents per patient) was chosen for patients at high surgical risk, with a minimum of two patent distal vessels, and proximal and distal necks of at least 1 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen articles were analyzed, published between 2005 and 2016 and comparing open surgery and endovascular surgery for treatment of PAAs. Thirteen of these articles were non-randomized studies [9][10][11][12][13][14][15][16][17][18][19][20][21] ; there was just one randomized clinical trial 22 and one comparative prospective study which followed up on the series studied by this randomized clinical trial. 23 The difficulty of establishing an adequate evidence level for any recommendation on treatment approach for PAAs is therefore clear.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative studies have shown primary patency rates in the range of 86.6 to 95.0% for endovascular techniques and 78.8 to 87.5% for open surgery using the saphenous vein as graft. 25 However, the 30 and 90-day reintervention rates after the initial endovascular procedure are considerably higher than after open surgery. 24…”
Section: Discussionmentioning
confidence: 99%